Toward a Buddhist Ecological Ethic of Care - Colin Harold Simonds (Religions, 2023)
This article thinks alongside the feminist ethic of care tradition to articulate a Tibetan Buddhist ethical approach to the more-than-human world. It begins by unpacking the characterization of Tibetan Buddhist ethics as a moral phenomenology before highlighting the major parallels between Buddhist moral phenomenology and the ethic of care tradition. Having made these parallels evident, this article then looks at how the ethic of care tradition has been applied to issues in animal ethics and environmental ethics to similarly think through how a Buddhist moral phenomenology might function in these more-than-human contexts. To further nuance this ecological application of Buddhist ethics, this article then takes up the question of veganism and argues that a Tibetan Buddhist care ethic would ideally adopt the positions of ethical veganism while also recognizing the socio-economic barriers to doing so in certain contexts. Ultimately, this article argues that when Buddhist moral phenomenology is applied to the more-than-human world, it presents as a Buddhist ecological ethic of care which recognizes the interconnected nature of duhkha, the necessity of approaching situations with care as one’s primary conative mode, and an emphasis on context, relationships, and positionality.